Uji Aktivitas Antibakteri Ekstrak Daun Karamuntin (Rhodomyrtus tomentosa (Aiton) Hassk.) terhadap Bakteri Streptococcus mutans - Ramadhanty, Dewi Alfisyah; Lestari, Yulianita Pratiwi Indah; Nashihah, Siti (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2023)
Abstract: Indonesia has many medicinal plants that can used to treat various diseases. One of the plants is the leaves of karamunting (Rhodomyrtus tomentosa (Aiton) Hassk.). Traditionally, karamunting leaves are used as a treatment in dental caries, wound care, and scabies. This study was aimed to determine the antibacterial effect of karamunting leaves ethanol extract against Streptococcus mutans by the well method. The design of this study was experimental laboratory research. The sample was karamunting leaves ethanol extract. The extracts were evaluated for antibacterial activity against Streptococcus mutans using the well method with a concentration of 6,25%; 12,5%; 25%; and 50% w/v. The result showed karamunting leaves ethanol extract provided an antibacterial activity against Streptococcus mutans with an inhibition zone diameters of 17,7±0,0577; 22,6±0,2516; 25,3±0,1527; and 28,3±0,0577 mm. at the concentration of 6,25% w/v, 12,5% w/v, 25% w/v, and 50% w/v, respectively. karamunting leaves ethanol extract had significant antibacterial activity against Streptococcus mutans at the concentration 50% w/v with inhibition zone diameters of 28,3 mm.